Biocompatibility of Poly-Lactic Acid/Nanohydroxyapatite/Graphene Nanocomposites for Load Bearing Bone Implants. Issue 2 (1st February 2023) - Michael, Feven Mattews; Shee, Lim Siew; Raju, Gunasundari; Rustagi, Sarvesh; Walvekar, Rashmi; Chaudhary, Vishal; Khalid, Mohammad
Abstract : In this study, poly-lactic acid (PLA), nanohydroxyapatite (NHA), and graphene nanoplatelets (GNP) were blended to develop a nanocomposite material suitable for load-bearing bone implants with the potential for strain-sensing applications. The tensile properties and impact strength of the PLA-NHA nanocomposite were analyzed, as these are crucial biomechanical properties for load-bearing and strain-sensing applications. It was found that the impact strength decreased by 7.9% (0.05 wt% GNP) and 25.7% (0.1 wt% GNP) with increasing GNP loading compared to 0.01 wt% GNP. Besides, the biocompatibility of nanocomposites (PLA-NHA, PLA-mNHA, and PLA-mNHA-GNP) was evaluated through in-vitro analysis by attaching MG63 cells to the nanocomposites and observing their proliferation and differentiation over 7 and 21 days of incubation. The biocompatibility of the prepared nanocomposites was determined based on their ability to attach with MG63 cells, thus allowing the cells to proliferate and enhance their ability to differentiate. Results showed that the PLA-5wt%NHA nanocomposite provided better cell spreading compared to pure PLA, while the PLA-5wt%mNHA nanocomposite had the highest rate of cell proliferation. The biocompatibility of the nanocomposites was further confirmed by field emission scanning electron microscope (FESEM) imaging, MTT assays, and alkaline phosphatase (ALP) assays.